Fetal–neonatal exposure to antibiotics and NEC development: A systematic review and meta-analysis - Klerk, Daphne H.; van Avezaath, Lisanne K.; Loeffen, Erik A. H.; Hulscher, Jan B. F.; Kooi, Elisabeth M. W. (Frontiers in Pediatrics, 2023)
Background: Fetal and neonatal exposure to antibiotics may contribute to development of necrotizing enterocolitis (NEC) in preterm infants. This systematic review and meta-analysis investigates whether exposure to third trimester maternal antibiotics (MAB) and/or prolongation of empirical antibiotics (PEAB) are associated with NEC development in preterms. Method: We included observational and randomized-controlled studies including preterm or VLWB infants, from MEDLINE and EMBASE, published between 1990 and June 2021. Exposure was defined as 3rd trimester MAB and/or PEAB. Two reviewers independently performed study selection, data extraction and quality assessment. Results: Three cohort studies compared third trimester MAB with no antibiotics. MAB was associated with lower NEC incidence, unadjusted pooled OR is 0.57 (95%CI 0.35-0.93). Twelve cohort studies showed that PEAB was associated with an increased risk of NEC. Ten observational cohort studies show an unadjusted OR of 2.72 (1.65-4.47), two case-control studies show an unadjusted MD of 2.31 (0.94-3.68). Moderate to substantial heterogeneity was observed but decreased in studies with low risk of bias and high sample size. Conclusion: Evidence suggests an association between MAB and decreased risk of NEC and an association between PEAB and increased risk of NEC. Further studies should confirm these associations and explore causality.